Coupling fully resolved light particles with the lattice Boltzmann method on adaptively refined grids - Werner, Lukas; Rettinger, Christoph; Rüde, Ulrich (International Journal For Numerical Methods in Fluids, 2021)
The simulation of geometrically resolved rigid particles in a fluid relies on coupling algorithms to transfer momentum both ways between the particles and the fluid. In this article, the fluid flow is modeled with a parallel lattice Boltzmann method using adaptive grid refinement to improve numerical efficiency. The coupling with the particles is realized with the momentum exchange method. When implemented in plain form, instabilities may arise in the coupling when the particles are lighter than the fluid. The algorithm can be stabilized with a virtual mass correction specifically developed for the lattice Boltzmann method. The method is analyzed for a wide set of physically relevant regimes, varying independently the body-to-fluid density ratio and the relative magnitude of inertial and viscous effects. These studies of a single rising particle exhibit periodic regimes of particle motion as well as chaotic behavior, as previously reported in the literature. The new coupled lattice Boltzmann method is compared with available experimental and numerical results. This serves to validate the presented method and additionally it leads to new physical insight for some of the parameter settings.
Keywords: fluid-structure interaction; hydrodynamics; incompressible flow; lattice Boltzmann; mesh adaptation; stabilized method

Micromechanical framework for a 3D solid cohesion model –implementation, validation and perspectives - Sanayei, Mohammad; Farhat, Abbas; Luu, Li Hua; Werner, Lukas; Rettinger, Christoph; Philippe, Pierre; Cuéllar, Pablo (particles2021, 2021)
This article presents a solid cohesion model for the simulation of bonded granular assemblies in the frame of 3D discrete element approaches (DEM). A simple viscoplastic cohesion model for 2D geometries is extended to 3D conditions, while its yield criterion is generalized as a hyper-surface in the space of bond solicitations to include torsional moments. The model is then calibrated using experimental results of uniaxial traction at both the microscopic and macroscopic scales with an artificial granular cohesive soil. The paper finally presents some simulated results on the macromechanical sample traction application and briefly discusses the model's current limitations and promising prospects for subsequent works.
CRIS-Team Scopus Importer:2024-12-16
Keywords: DEM; Granular Cohesive Materials; Macromechanical Sample Strength; Micromechanical Tensile Failure